TEACHERS’ DIRECTIVE SPEECH ACTS IN EFL CLASSROOM INTERACTIONS - Nabila Faizah Nur’aini Siregar; Anni Holila Pulungan (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2022)
This study aims to observe the implementation of directive speech acts by English teachers in teaching and learning activities in MAN 2 Model Medan. The objectives of this study are to analyze the types of directive speech acts, the way directive speech acts are used by teachers, and the reasons teachers perform directive speech acts in EFL (English as a Foreign Language) classroom interactions. The research methodology was descriptive qualitative. The data were collected by observation and interview. The data in this study are sentences spoken by the teacher that contain directive speech acts. The data sources are two teachers who teach English subjects in X IPA 4 and XI IPA 5 classes. The researcher found three results from this study, they are 1) Teachers use three types of directive speech acts: command (48 utterances), request (7 utterances), and suggestion (10 utterances). Command is the most frequent of all the types of directive speech acts performed by teachers in EFL classroom interactions since teachers always use this type to attract students’ attention and convey their instructions during the teaching-learning process; 2) In performing directive speech acts, teachers use two ways: direct (51 times) and indirect (14 times). Direct directive speech acts are the most frequent of all the ways of directive speech acts used by teachers in EFL classroom interactions since teacher often used utterances that had no implicit meaning and immediately understood and responded to by students; 3) The reasons teachers perform directive speech acts in EFL classroom interactions are because there are many functions in using directive speech acts. Commands were to attract students’ attention (Attention-getter), to test students’ knowledge or understanding (Elicitation), and to ask students to do something (Instruction). Requests were to attract students’ attention (Attention-getter), to test students’ knowledge (Elicitation), and to make students do what the teacher instructs (Instruction). Then, Suggestions were to suggest and to advise students on what should do (Suggestion/Advice).Keywords: Directive Speech Acts, Teaching and Learning Activity, EFL Classroom